Unilateral Pterional Polycraniosynostosis Treated with Craniectomy and Helmet Therapy. (February 2017) - Law, Jenaleen; Marucci, Damian D.; Gates, Robert J.; Fowler, Adam
Abstract : Summary: Craniosynostosis is a condition in which one or more of the cranial sutures have fused prematurely, affecting the growth pattern and contours of the infant skull. The pterion is the junction of temporal, frontal, parietal, and sphenoid bones of the skull. We present a case of unilateral pterional craniosynostosis, which was treated with strip craniectomy and helmet therapy. Abstract : Supplemental Digital Content is available in the text.